2006
DOI: 10.2337/db06-0063
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Interleukin-6 Levels Are Independently Associated With Insulin Secretion in a Cohort of Italian-Caucasian Nondiabetic Subjects

Abstract: We have investigated the relationships between plasma interleukin-6 (IL-6) levels and insulin sensitivity and insulin secretion in a cohort of Italian-Caucasian glucosetolerant subjects. Insulin sensitivity was assessed by euglycemic-hyperinsulinemic clamp, and first-phase insulin secretion was measured by intravenous glucose tolerance test. Fasting plasma IL-6 concentration was negatively correlated with the rate of insulin-stimulated glucose disposal (M) (P ‫؍‬ 0.001). The correlation remained statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 25 publications
1
22
1
1
Order By: Relevance
“…For example, elevated IL-6 serum level has been found to be associated with higher fasting and postload insulin level in healthy human population, implying that IL-6 may encourage insulin secretion (29,30). In line with this suggestion, it was revealed that IL-6 might directly stimulate insulin secretion from rat pancreatic islets (31) as well as from cultures of these cells in vitro (32).…”
Section: Discussionsupporting
confidence: 61%
“…For example, elevated IL-6 serum level has been found to be associated with higher fasting and postload insulin level in healthy human population, implying that IL-6 may encourage insulin secretion (29,30). In line with this suggestion, it was revealed that IL-6 might directly stimulate insulin secretion from rat pancreatic islets (31) as well as from cultures of these cells in vitro (32).…”
Section: Discussionsupporting
confidence: 61%
“…Proinflammatory cytokine tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) and oxidative stress are widely recognized markers of vascular inflammation (Andreozzi et al, 2006;Kern, Ranganathan, Li, Wood, & Ranganathan, 2001;Rui et al, 2001;Singh, Devraj, & Jialal, 2005). The levels of these cytokines and oxidative stress are elevated in the blood of many diabetic patients (Jain, Kannan, Lim, McVie, & Bocchini, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…The reason for this discrepancy is currently unclear. Interestingly, it was recently reported that circulating IL-6 levels correlated positively with insulin levels in man and that this was unrelated to degree of insulin resistance [47]. One possible mechanism for this could be AMPK activation by IL-6.…”
Section: Discussionmentioning
confidence: 98%